Ekumeniczna działalność świeckich dworzan cesarza Justyna I (518-527) w świetle ich korespondencji z Rzymem - Koczwara, Stanisław (Vox Patrum, 2003)
Taking over the throne in 518 by the Emperor Justin I impacted on the emperor’s court to change politics in order to support of the Chalcedonian Synod. The most important thing was that, the Emperor as well as his supporting courtiers, took into consideration the main role of the Apostolic See in protecting truth religion. Courtly guardians of Chalcedon such as the Empress Eufemia, Justinian’s relative a commander of the Court Guard Vitalian, maids of honour: Anastasia, Palmacja Julianan Anicia, Celer, Pompeius, German were successful in making an ecumenical effort to restore the union in the Catholic Church.